The threat of 'currency wars': A European perspective - Zsolt Darvas; Jean Pisani-Ferry (Hungarian Academy of Sciences, Institute of Economics, 2011)
The 'currency war', as it has become known, has three aspects: 1) the inflexible pegs of undervalued currencies; 2) recent attempts by floating exchange-rate countries to resist currency appreciation; 3) quantitative easing. Europe should primarily be concerned about the first issue, which relates to the renewed debate about the international monetary system. The attempts of floating exchange-rate countries to resist currency appreciation are generally justified while China retains a peg. Quantitative easing cannot be deemed a 'beggar-thy-neighbour' policy as long as the Fed's policy is geared towards price stability. Current US inflationary expectations are at historically low levels. Central banks should come to an agreement about the definition of price stability at a time of deflationary pressures. The euro's exchange rate has not been greatly impacted by the recent currency war; the euro continues to be overvalued, but less than before.
Keywords: E52; E58; F31; F33; 330; currency war; quantitative easing; currency intervention; international monetary system; Wechselkurspolitik; Internationales Währungssystem; Wechselkurs; Euro; EU-Staaten